Allogeneic ‘off‐the‐shelf’ SARS‐CoV‐2‐specific adoptive T‐cell therapy for refractory viral infection and end organ disease - Andrea S Henden; Katie E Lineburg; Archana Panikkar; Arushi Mahajan; Ricky Nelles; Emma Wright; Pauline Crooks; Jyothy Raju; Laetitia Le Texier; Srividhya Swaminathan; Leone Beagley; Shannon Best; et al. (Clinical & Translational Immunology)
Abstract Objectives Despite the effective roll‐out of COVID‐19 vaccines, immunocompromised patients have a higher risk of morbidity and mortality following SARS‐CoV‐2 infection. Allogeneic adoptive T‐cell immunotherapy is now established as an effective approach to treat viral diseases in immunocompromised patients. The objective of this study was to assess the safety of allogeneic virus‐specific T‐cell therapy in patients with COVID‐19. Methods Using a repository of SARS‐CoV‐2‐specific T cells generated from healthy exposed volunteers, we conducted an open‐label phase I trial to assess the feasibility and safety of allogeneic SARS‐CoV‐2‐specific T cells in immune‐compromised cancer patients with COVID‐19. Results Six participants at risk of severe COVID‐19 were enrolled and received SARS‐CoV‐2‐specific T‐cell therapy within 4 days of recruitment. The first five participants who received two infusions of allogeneic SARS‐CoV‐2‐specific T‐cell therapy experienced no adverse events following treatment. Four of the six participants showed improvement in viral load following treatment and were alive at 12‐week follow‐up. One participant died 6 days after their second infusion, because of established pulmonary parenchymal damage following prolonged COVID infection. Another, who had underlying lupus nephritis, developed cytokine release syndrome and diffuse alveolar haemorrhage following a single infusion and was withdrawn from the study. They subsequently recovered from this serious adverse event. Conclusion Allogeneic SARS‐CoV‐2‐specific T‐cell therapy provides a platform to rapidly administer T cells to high‐risk COVID‐19 patients. It was associated with a reduced viral load and increased SARS‐CoV‐2‐specific T‐cell responses in the majority of treated patients.